Economic analysis of antibiotics use and vaccine program in commercial broiler farming of Tangail district in Bangladesh - Sultan, S; Begum, R; Rahman, MA; Ahmed, MJU; Islam, MM; Haque, S (Progressive Agriculture, 2017)
The present study was conducted to investigate the status of current antibiotics use and vaccine application program in commercial broiler farming, to understand about the current market scenario of antibiotics and vaccine related products and to identify the major problems of broiler farming and suggestions for its improvements. For achieving these objectives, 50 broiler farms and 20 antibiotics-vaccine products sellers were selected purposively from 5 selected unions of Sakhipur upazila in Tangail district. In the study area, 42% respondent had a slim idea about residual effect of antibiotics. Most of the farmers in the visited area used almost same types of antibiotics. Among the farms surveyed, 98% farms practiced proper vaccination. Among the 50 farmers, 66% farmers had idea about sound vaccination program and 98% farmer thought that vaccination is essential for their farming. In the study area, 70% farmers got their antibiotics and vaccine from dealer. The study showed that antibiotic cost is only 3.53% and vaccination cost is 1.06% of the total cost. Regarding the antibiotics use, results were alarming and found that 100% respondents used antibiotics in broiler production. Both positive and negative significant correlations were observed for different parameters. The problems related to present antibiotics and vaccination program and their probable solutions suggested by broiler farmers were also focused in this study. Progressive Agriculture 27 (4): 490-501, 2016